2017
DOI: 10.1002/lno.10766
|View full text |Cite
|
Sign up to set email alerts
|

Thermal reaction norms of a subtropical and a tropical species of Diaphanosoma (cladocera) explain their distribution

Abstract: Species distribution boundaries are often associated with aspects of climate and modified by competitive interactions. In the tropical region, Diaphanosoma is the most diverse genus of Cladocera. Diaphanosoma dubium is widely distributed in China, whereas the tropical Diaphanosoma excisum is restricted to the islands off the south China coast. The mean temperature of the coldest month at the northern limit of its distribution is 15°C. We studied the effect of temperature (10–40°C) on life history traits of clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
(169 reference statements)
0
15
0
Order By: Relevance
“…are thermophilic species (Lazareva 2012;Lazareva and Bolotov 2013), exhibiting a short generation time, large clutch size, and consequently a large intrinsic rate of increase at temperatures between 23 C and 29 C (Han et al 2011). Pajk et al (2018) also showed that intrinsic rates of increase in Diaphanosoma clones collected from southern China (20-28 N) were quite low below 20 C and optimum at 3 C. Usually, surface water temperatures rapidly increased in June every year in Lake Biwa (Kagami et al 2006). Average water temperature within the mixed layer, that is, above 20 m, exceeded 20 C from July to October, and high biomass of this species was mostly recorded during those months ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…are thermophilic species (Lazareva 2012;Lazareva and Bolotov 2013), exhibiting a short generation time, large clutch size, and consequently a large intrinsic rate of increase at temperatures between 23 C and 29 C (Han et al 2011). Pajk et al (2018) also showed that intrinsic rates of increase in Diaphanosoma clones collected from southern China (20-28 N) were quite low below 20 C and optimum at 3 C. Usually, surface water temperatures rapidly increased in June every year in Lake Biwa (Kagami et al 2006). Average water temperature within the mixed layer, that is, above 20 m, exceeded 20 C from July to October, and high biomass of this species was mostly recorded during those months ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…D. excisum (clone D) was collected from Hedi reservoir, Zhanjiang, China (N21°85', E110°31'). The two clones chosen were each the best performing clone of its species from our previous life history experiments with 16 Diaphanosoma clones [25]. We measured their life history traits (net reproductive rate (R 0 ), intrinsic rate of population increase (r)) under a temperature range from 10°C to 40°C.…”
Section: Life History and Temperature Nichementioning
confidence: 99%
“…We measured their life history traits (net reproductive rate (R 0 ), intrinsic rate of population increase (r)) under a temperature range from 10°C to 40°C. 40℃ was estimated to be above the critical thermal maximum (CT max ), while 10℃was estimated to be below the critical thermal minimum (CT min ) [25]. Life table experiments were conducted at 15, 20, 25, 30, 34, and 38 °C.…”
Section: Life History and Temperature Nichementioning
confidence: 99%
See 1 more Smart Citation
“…The effects of temperature on biological processes are usually summarized in a thermal performance curve (Schulte et al 2011), and when temperatures are too high, thermal stress prevents growth and reproduction of organisms. Understanding thermal tolerance curves and ecological interactions has important implications for predicting geographical distributions of species in face of global climate change (Pajk et al 2018).…”
Section: Life-history Traitsmentioning
confidence: 99%